PENGARUH MANAJERIAL ABILITY, LEVERAGE DAN STRUKTUR KEPEMILIKAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Niawati Niawati; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study was to determine the effect of managerial ability, leverage and ownership structure on tax avoidance of transport companies listed on the Indonesia Stock Exchange (IDX) for the period 2014 – 2018. The population in this study was transportation companies listed on the Indonesia Stock Exchange (IDX) period 2014 -2018. Samples selected using purposive sampling and the number of samples obtained were 7 companies based on predetermined criteria. This research uses multiple linier regression models. The results showed that managerial ability, leverage and ownership structure variables had a positive and significant effect on tax avoidance on transport companies listed on the Indonesia Stock Exchange (BEI) for the period 2014- 2018. Keywords : Manajerial Ability, Leverage, Ownership Structure, Tax Avoidance